Apheresis therapies for NMOSD attacks: a retrospective study of 207 therapeutic interventions - Kleiter, Ingo Wolfram; Wildemann, Brigitte (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2018)
To analyze whether 1 of the 2 apheresis techniques, therapeutic plasma exchange (PE) or immunoadsorption (IA), is superior in treating neuromyelitis optica spectrum disorder (NMOSD) attacks and to identify predictive factors for complete remission (CR).
Gesehen am 31.10.2019